Teaching general practitioners and doctors-in-training to discuss advance care planning: evaluation of a brief multimodality education programme. Issue 3 (20th May 2014) - Detering, Karen; Silvester, William; Corke, Charlie; Milnes, Sharyn; Fullam, Rachael; Lewis, Virginia; Renton, Jodie
Abstract : Objective: To develop and evaluate an interactive advance care planning (ACP) educational programme for general practitioners and doctors-in-training. Design: Development of training materials was overseen by a committee; informed by literature and previous teaching experience. The evaluation assessed participant confidence, knowledge and attitude toward ACP before and after training. Setting: Training provided to metropolitan and rural settings in Victoria, Australia. Participants: 148 doctors participated in training. The majority were aged at least 40 years with more than 10 years work experience; 63% had not trained in Australia. Intervention: The programme included prereading, a DVD, interactive patient e-simulation workshop and a training manual. All educational materials followed an evidence-based stepwise approach to ACP: Introducing the topic, exploring concepts, introducing solutions and summarising the conversation. Main outcome measures: The primary outcome was the change in doctors' self-reported confidence to undertake ACP conversations. Secondary measures included pretest/post-test scores in patient ACP e-simulation, change in ACP knowledge and attitude, and satisfaction with programme materials. Results: 69 participants completed the preworkshop and postworkshop evaluation. Following education, there was a significant change in self-reported confidence in six of eight items (p=0.008 –0.08). There was a significant improvement (p<0.001) in median scores on the e-simulation (pre 7/80, post 60/80). There were no significant differences observed in ACP knowledge following training, and most participants were supportive of patient autonomy and ACP pretraining. Educational materials were rated highly. Conclusions: A short multimodal interactive education programme improves doctors' confidence with ACP and performance on an ACP patient e-simulation.